Effectiveness of marketing mix activities in engineering companies in the Czech Republic - František Milichovský (DANUBE: Law, Economics and Social Issues Review, 2017)
The effectiveness of marketing activities has become important, especially in the industrial environment. In an industrial environment, there is a prerequisite for the success of strategic marketing objectives in relation to corporate strategy. The main aim of the paper is to determine whether the realization of marketing activities is influenced by corporate size. For this reason, a questionnaire survey was used, focusing on engineering companies operating in the Czech Republic. To process the results of the questionnaire survey, both basic types of descriptive statistics and Pearson's chi-square test were used on the selected dataset. The data were processed using the statistical program IBM SPSS Statistics 22. The conclusions provide characteristics of the limitations of research and its potential further direction.
Keywords: 330; Marketing Mix; Marketing Effectiveness; Corporate Size; Engineering